Gita Wirjawan’s Use of Politeness in Requesting and Using Addressing Terms in Two Endgame Podcasts - Olivia Faustine Supriyono; Esther Harijanti Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2023)
This research examines politeness in two Endgame podcasts, focusing on Gita Wirjawan's request and the use of address terms with a minister and a non-government employee. The writer analyzes politeness expressed by Gita Wirjawan in two podcasts on his channel using First-Order Politeness by Watts (2003) and the Indonesian (Javanese) politeness principle by Suseno (2001) and Kuntjara (2009). A descriptive qualitative approach is employed in this study. The analysis shows that Gita often uses direct language for requests, utilizes the term 'you' to blur their distance. The findings show that Gita wanted to look neutral with someone who has the same rank and tended to appear to have a lower rank when he talks with someone with a higher rank. In conclusion, differences in rank influence how people communicate.